Ensemble noise-aided bit flipping decoding of low-density parity-check codes - Shtompel, Mykola; Shefer, Oleksandr (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2026)
Moderate-length low-density parity-check codes are incorporated to increase the data transmission reliability and the energy gain in the next generation wireless communication systems. The paper proposes ensemble decoding based on reduced-complexity noise-aided gradient descent bit flipping algorithm. Block diagram and pseudocode of this approach were presented. The decoding by each constituent noise-aided bit flipping decoder is performed independently and in parallel mode. The ensemble size and the chosen noise scale values are key parameters of this decoding framework. The simulation results confirmed the efficiency of the proposed noise-aided ensemble decoder. It was shown that the increasing of ensemble size leads to improve the error performance. The average number of decoding iterations is acceptable in high signal-to-noise ratio region. The application of the presented decoding algorithm will improve the data transmission reliability under low-latency requirements in the next generation wireless technologies.